The Effectiveness of the Cogan, Goldhammer, and Glickman Clinical Supervision Approach: An Adaptive Study for the Development of Teachers' Professional Competence in Elementary Schools - Handayani, Anita; Sudadi, Sudadi; Baitaputra, Moh. Holil (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
This study aims to analyze the effectiveness of various approaches in clinical supervision based on the Cogan, Goldhammer, and Glickman models, as well as their impact on improving teachers' professional competence in primary schools. Clinical supervision has proven to be an effective method in supporting the development of teaching skills through a structured process of observation and feedback. The Cogan and Goldhammer model offers a systematic approach in the pre-observation, observation, and post-observation cycles that aim to provide direct feedback to teachers. Meanwhile, the Glickman model introduces an adaptive approach that adapts the supervision style—directive, non-directive, or collaborative—to the individual needs of the teacher based on his or her level of commitment and abstraction ability. This study uses a qualitative approach through observation, in-depth interviews, and document analysis to evaluate the implementation of all three models of clinical supervision in several primary schools. The results show that the adaptive approach in the Glickman model, when applied well, can improve the effectiveness of supervision by accommodating the unique characteristics of each teacher. This model is considered more flexible and able to have a more significant impact than the Cogan and Goldhammer models in improving the quality of teaching. This study suggests the use of a more adaptive clinical supervision model to meet the needs of diverse teachers' professional coaching, in order to improve the overall quality of learning in elementary schools